2020
DOI: 10.3390/jpm10030082
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Predict 30-Day Hospital Readmissions in Patients with Atrial Fibrillation Undergoing Catheter Ablation

Abstract: Atrial fibrillation (AF) cases are expected to increase over the next several decades, due to the rise in the elderly population. One promising treatment option for AF is catheter ablation, which is increasing in use. We investigated the hospital readmissions data for AF patients undergoing catheter ablation, and used machine learning models to explore the risk factors behind these readmissions. We analyzed data from the 2013 Nationwide Readmissions Database on cases with AF, and determined the relative import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Machine learning algorithms could deeply mine and analyze big data, and it had been widely used in disease predictions and prognostication (15)(16)(17). RF is one of the widely used algorithms in machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning algorithms could deeply mine and analyze big data, and it had been widely used in disease predictions and prognostication (15)(16)(17). RF is one of the widely used algorithms in machine learning.…”
Section: Discussionmentioning
confidence: 99%
“… 103 focused on a more specific risk stratification model of young patients with hypertension. Hospital readmissions data for AF patients undergoing catheter ablation was investigated by Hung et al ., to estimate the risk factors behind 90- 104 and 30-day 105 hospital readmissions.…”
Section: Risk Prediction Modelling With Ai/ml Methodsmentioning
confidence: 99%
“…However, only a study reported risk model derived from over 1,000 patient population (6), but the follow-up duration was relatively short of investigating the progression to permanent AF (mean 2.5 years). Based on a variety of sources of complex patient information, including electronic medical records (EMRs) and imaging data, artificial intelligence (AI) has been used to detect AF and to predict ablation outcomes (7)(8)(9)(10)(11)(12). Furthermore, AI has been suggested for predicting invasive parameters or invasive cardiovascular outcomes (13).…”
Section: Introductionmentioning
confidence: 99%